All-solid-state battery and manufacturing method thereof

By using a non-polar solvent to immerse the positive electrode or negative electrode active material layer and dry it in an all-solid state battery, the problem of solvent penetration into the electrode is solved, the interface resistance is reduced, and the battery performance is improved.

CN120569834APending Publication Date: 2025-08-29LG ENERGY SOLUTION LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202480008809.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-08-06
Filing Date
2024-08-07
Publication Date
2025-08-29

AI Technical Summary

Technical Problem

In all-solid-state batteries, when the sulfide-based solid electrolyte membrane is coated on the electrode, the solvent may penetrate into the electrode, resulting in an increase in interface resistance and affecting the battery performance.

Method used

A non-polar solvent is used to impregnate the positive electrode or negative electrode active material layer, and a sulfide-based solid electrolyte film is formed after drying to prevent the solvent from penetrating into the electrode and reduce the interface resistance.

Benefits of technology

By preventing solvents and particles from accumulating at the interface, the interface resistance is reduced and the performance of all-solid-state batteries is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120569834A_ABST
    Figure CN120569834A_ABST
Patent Text Reader

Abstract

The present invention relates to an all-solid-state battery and a method for manufacturing the same, and more specifically, the performance of the all-solid-state battery can be improved by reducing the interface resistance between a sulfide-based solid electrolyte membrane and an electrode by ensuring that the inside of the electrode adjacent to the sulfide-based solid electrolyte membrane does not contain a solvent or the inside of the electrode contains a non-polar solvent.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application claims priority from Korean Patent Application No. 10-2023-0106058, filed on August 14, 2023, and Korean Patent Application No. 10-2024-0104404, filed on August 6, 2024, the disclosures of which are incorporated herein by reference in their entirety. Technical Field

[0002] The present disclosure relates to all-solid-state batteries and methods for manufacturing the same. Background Art

[0003] Various batteries are being researched to overcome the limitations of current lithium secondary batteries in capacity, safety, output, scale-up, and miniaturization.

[0004] Representative examples include metal-air batteries, which have a very high theoretical capacity compared to lithium secondary batteries; all-solid-state batteries, which are safe and explosion-proof; supercapacitors, which offer high output; NAS batteries or redox flow batteries (RFBs) for large-scale applications; and thin-film batteries for miniaturization. These technologies are undergoing ongoing research in academia and industry.

[0005] All-solid-state batteries use solid electrolytes instead of the liquid electrolytes used in conventional lithium secondary batteries. Because no flammable solvents are used in the battery, there is no possibility of fire or explosion caused by the decomposition reaction of conventional electrolytes, which greatly improves safety. It also has the advantage of being able to use lithium metal or lithium alloys as the negative electrode material, which can significantly increase the battery's energy density relative to mass and volume.

[0006] Research is underway to realize all-solid-state batteries using sulfide-based solid electrolytes, which, among various solid electrolytes, have high ionic conductivity and ductility.

[0007] All-solid-state batteries containing sulfide-based solid electrolytes are typically manufactured by placing a sulfide-based solid electrolyte membrane between the positive electrode and the negative electrode, followed by pressing under high pressure. To manufacture an all-solid-state battery comprising a positive electrode, a sulfide-based solid electrolyte membrane, and a negative electrode, a sulfide-based solid electrolyte membrane can be used, typically in a free-standing form, or a process can be performed in which the sulfide-based solid electrolyte membrane is transferred to an electrode, or the electrode is coated with a sulfide-based solid electrolyte. Coating the electrode with a sulfide-based solid electrolyte membrane has the advantages of improving process efficiency and enabling the realization of a thin solid electrolyte membrane.

[0008] However, if a sulfide-based solid electrolyte membrane is coated on an electrode, the solvent in the electrolyte slurry may penetrate into the electrode, and small and light electrolyte particles or binder may be squeezed out and located at the interface between the electrode and the sulfide-based solid electrolyte membrane, resulting in an increase in interfacial resistance.

[0009] Therefore, when a sulfide-based solid electrolyte membrane is overcoated on an electrode, a technology capable of preventing the electrolyte slurry from being squeezed out and preventing the solvent contained in the electrolyte slurry from penetrating into the electrode is required.

[0010] [Prior art literature]

[0011] [Patent Document]

[0012] (Patent Document 1) Japanese Patent 4046376 Summary of the Invention

[0013] [Technical Issues]

[0014] The inventors of the present disclosure have conducted extensive research to solve the above-mentioned problems and have found that in an all-solid-state battery including a positive electrode, a sulfide solid electrolyte membrane and a negative electrode, if the positive electrode or the negative electrode to be coated with a sulfide solid electrolyte membrane is pre-impregnated with a non-polar solvent and then dried to be solvent-free, or if the non-polar solvent is retained, the solvent in the sulfide solid electrolyte slurry used for coating will be prevented from being squeezed into the positive electrode or the negative electrode, thereby reducing the interface resistance between the electrode and the electrolyte and improving the battery performance.

[0015] Therefore, an object of the present disclosure is to provide an all-solid-state battery in which the interface resistance between the positive electrode or the negative electrode and the sulfide-based solid electrolyte membrane is reduced, thereby improving battery performance.

[0016] Another object of the present disclosure is to provide a method for manufacturing the all-solid-state battery.

[0017] [Technical solution]

[0018] In order to achieve the above-mentioned objectives, the present disclosure provides an all-solid-state battery, which includes a positive electrode, a negative electrode and a sulfide solid electrolyte membrane arranged therebetween, wherein the positive electrode active material layer or the negative electrode active material layer included in the positive electrode or the negative electrode is solvent-free or contains a non-polar solvent, and wherein the non-polar solvent has a dielectric constant of less than 10.

[0019] In one example of the present disclosure, the non-polar solvent may include at least one selected from the group consisting of toluene, xylene, anisole, benzene, hexane, heptane, nonane, decane, dibromomethane, dichloromethane, chloroform, butyrate, and acetate.

[0020] In one example of the present disclosure, the content of the non-polar solvent may be 100 to 2000 ppm.

[0021] In one example of the present disclosure, the sulfide-based solid electrolyte membrane may include a sulfide-based solid electrolyte having an argyrodite structure.

[0022] In one embodiment of the present disclosure, the sulfide-based solid electrolyte may include Li 7-x PS 6-x A x , wherein A is Cl, Br, I, Sn or a combination thereof, and x is 0≤x≤2.

[0023] In one example of the present disclosure, the negative electrode active material layer may include lithium metal, or may be free of an anode coating.

[0024] The present disclosure also provides a method for forming a sulfide solid electrolyte membrane, the method comprising: (a) impregnating a positive electrode active material layer or a negative electrode active material layer contained in a positive electrode or a negative electrode with a non-polar solvent; (b) overcoating the positive electrode active material layer or the negative electrode active material layer obtained in the above step (a) with a slurry for forming a sulfide solid electrolyte membrane to form a sulfide solid electrolyte membrane; and (c) drying the sulfide solid electrolyte membrane obtained in the above step (b), wherein the dielectric constant of the non-polar solvent is less than 10.

[0025] In one example of the present disclosure, a slurry for forming a sulfide-based solid electrolyte membrane may be prepared by mixing a sulfide-based solid electrolyte in a solvent.

[0026] In one example of the present disclosure, the solvent is a non-polar solvent, and the non-polar solvent may have a dielectric constant of 10 or less.

[0027] In one example of the present disclosure, the slurry may further include a binder.

[0028] In one example of the present disclosure, the outer coating may be performed by rod coating, roller coating, gravure coating, knife coating, slot die coating, slurry coating or extrusion coating.

[0029] In one example of the present disclosure, the drying in step (c) may be performed at 40°C to 90°C.

[0030] [Beneficial effects]

[0031] According to the present disclosure, in an all-solid-state battery formed by coating a sulfide solid electrolyte membrane on a positive electrode or a negative electrode, the interior of the positive electrode or the negative electrode is solvent-free or contains a non-polar solvent, so that the solvent in the slurry used to coat the sulfide solid electrolyte membrane is squeezed out and prevented from penetrating into the interior of the positive electrode or the negative electrode. Therefore, the component particles squeezed together with the solvent in the slurry will not be squeezed out, and the accumulation of particles at the interface can be prevented. In addition, since these particles do not accumulate at the interface between the positive electrode or the negative electrode and the sulfide solid electrolyte membrane, the interface resistance is reduced, which can improve the performance of the all-solid-state battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 These are photographs showing experimental results of selecting a solvent that does not cause a side reaction with a sulfide-based solid electrolyte in an experimental example of the present disclosure.

[0033] Figure 2 1 is a scanning electron microscope (SEM) photograph of the interface between the non-anode coating layer and the sulfide-based solid electrolyte membrane in the all-solid-state batteries prepared in Example 1 and Comparative Example 1 of the present disclosure. DETAILED DESCRIPTION

[0034] It can be manufactured by the following methods. For example, methods such as pressing, coating, or deposition can be used. The negative electrode of the present disclosure also includes the case where the battery is assembled without a lithium film on the negative electrode current collector, and then a metallic lithium film is formed on the metal plate during initial charging.

[0035] In one example of the present disclosure, a positive electrode in an all-solid-state battery includes a positive electrode active material layer, wherein the positive electrode active material layer may be formed on one side of a positive electrode current collector.

[0036] The positive electrode active material layer includes a positive electrode active material, a conductive material, and a binder. In addition, the positive electrode active material layer may further include a sulfide-based solid electrolyte.

[0037] In addition, the positive electrode active material may be any material that can reversibly absorb and release lithium ions, but is not particularly limited thereto, for example: layered compounds such as lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2) Li[Ni x Co y Mn z M v ]O2 (wherein M is any one or more elements selected from the group consisting of Al, Ga and In; 0.3≤x<1.0, 0≤y, z≤0.5, 0≤v≤0.1, and x+y+z+v=1), Li(Li a M b-a-b' M' b' )O 2-c Ac (wherein 0≤a≤0.2, 0.6≤b≤1, 0≤b'≤0.2, 0≤c≤0.2; M comprises at least one selected from the group consisting of Mn, Ni, Co, Fe, Cr, V, Cu, Zn and Ti; M' comprises at least one selected from the group consisting of Al, Mg and B; and A comprises at least one selected from the group consisting of P, F, S and N) or a compound substituted with one or more transition metals; lithium manganese oxide, such as a compound of the formula Li 1+y Mn 2-y Compounds of LiMnO4 (wherein y is 0 to 0.33), LiMnO3, LiMn2O3 or LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, LiFe3O4, V2O5 or Cu2V2O7; compounds of the formula LiNi 1-y Ni-type lithium nickel oxide represented by MyO2 (wherein M is Co, Mn, Al, Cu, Fe, Mg, B or Ga, y is 0.01 to 0.3); 2-y M y Lithium manganese composite oxide represented by Li2Mn3MO8 (wherein M is Co, Ni, Fe, Cr, Zn or Ta, and y is 0.01 to 0.1) or Li2Mn3MO8 (wherein M is Fe, Co, Ni, Cu or Zn); LiMn2O4 in which a portion of Li is replaced by alkaline earth metal ions; disulfide; Fe2(MoO4)3; etc., but not limited to these.

[0038] In addition, based on the total weight of the positive electrode active material layer, the content of the positive electrode active material may be 60 to 90 weight %. Specifically, the content of the positive electrode active material may be 60 weight % or more, 65 weight % or more, or 70 weight % or more, 80 weight % or less, 85 weight % or less, or 90 weight % or less. If the content of the positive electrode active material is less than 60 weight %, the battery performance may be reduced, and if the content is greater than 90 weight %, the mass transfer resistance may increase.

[0039] Otherwise, the binder is as described above for the negative electrode.

[0040] In addition, the conductive material is as described above for the negative electrode.

[0041] The specific material of the sulfide-based solid electrolyte can be the same as that described for the sulfide-based solid electrolyte contained in the sulfide-based solid electrolyte membrane. However, considering the ion conductivity characteristics, the content of the sulfide-based solid electrolyte in the positive electrode active material layer can be 5% to 25% by weight, and more specifically, it can be 5% by weight or more, 8% by weight or more, 10% by weight or more, 15% by weight or less, 20% by weight or less, or 25% by weight or less.

[0042] In addition, the positive electrode current collector supports the positive electrode active material layer and serves to transfer electrons between the external lead and the positive electrode active material layer.

[0043] The positive electrode current collector is not particularly limited as long as it has high electronic conductivity and does not cause chemical changes in the all-solid-state battery. For example, as the positive electrode current collector, copper, stainless steel, aluminum, nickel, titanium, palladium, calcined carbon, copper or stainless steel with a surface treated with carbon, nickel or silver, aluminum-cadmium alloy, etc. can be used.

[0044] The positive electrode current collector may have a microscopic roughness or a three-dimensional porous structure on the surface of the positive electrode current collector to enhance the bonding force with the positive electrode active material layer. Therefore, the positive electrode current collector may include various forms, such as films, sheets, foils, screens, nets, porous materials, foams, non-woven materials, etc.

[0045] The positive electrode as described above can be manufactured according to a conventional method. More specifically, a positive electrode active material layer-forming composition prepared by mixing a positive electrode active material with a conductive material and a binder in an organic solvent is coated on a positive electrode current collector and dried, and optionally compression molded on the current collector to increase the electrode density. In this case, it is preferred to use an organic solvent that can evenly disperse the positive electrode active material, binder and conductive material and easily evaporate. Specifically, examples include acetonitrile, methanol, ethanol, tetrahydrofuran, water and isopropanol.

[0046] Manufacturing method of all-solid-state battery

[0047] The present disclosure also relates to methods of manufacturing all-solid-state batteries.

[0048] The method for forming an all-solid-state battery comprises: (a) impregnating a positive electrode active material layer or a negative electrode active material layer contained in a positive electrode or a negative electrode with a non-polar solvent; (b) overcoating the positive electrode active material layer or the negative electrode active material layer obtained in step (a) with a slurry for forming a sulfide-based solid electrolyte membrane to form a sulfide-based solid electrolyte membrane; and (c) drying the sulfide-based solid electrolyte membrane obtained in step (b). The dielectric constant of the non-polar solvent may be 1 to 10.

[0049] Hereinafter, the method for manufacturing an all-solid-state battery of the present disclosure will be described in more detail through various steps.

[0050] The types, properties, and weights of the materials contained in the positive electrode, negative electrode, and sulfide-based solid electrolyte membrane in the method for manufacturing an all-solid-state battery are the same as those described above.

[0051] In one example of the present disclosure, in the above step (a), the positive electrode active material layer or the negative electrode active material layer contained in the positive electrode or the negative electrode may be impregnated with a non-polar solvent.

[0052] The positive electrode may be prepared by coating a slurry for forming a positive electrode active material layer on a positive electrode current collector and drying it.

[0053] In addition, the negative electrode can be prepared by coating a slurry for forming a negative active material layer on a negative current collector and drying it. The negative active material layer may be an anode-free coating layer that does not include a negative active material.

[0054] The method for impregnating the positive electrode active material layer or the negative electrode active material layer with a non-polar solvent is not particularly limited, as long as the non-polar solvent can be sprayed and impregnated. For example, using a micropipette or a sprayer, an appropriate amount of the non-polar solvent can be sprayed onto the positive electrode active material layer or the negative electrode active material layer to impregnate it.

[0055] In one example of the present disclosure, in the above step (b), a slurry for forming a sulfide-based solid electrolyte membrane can be applied on the positive electrode active material layer or the negative electrode active material layer obtained in the above step (a) to form a sulfide-based solid electrolyte membrane.

[0056] The slurry for forming the sulfide-based solid electrolyte membrane is prepared by mixing sulfide-based solid electrolyte particles with a solvent, wherein the solvent may be a non-polar solvent having a dielectric constant of 1 to 10. The non-polar solvent may include at least one selected from the group consisting of butyrate, acetate, xylene, and anisole. The slurry may be formulated to have a solid content of 45 to 60% by weight.

[0057] Furthermore, when preparing the slurry for forming the sulfide-based solid electrolyte membrane, a binder may be further mixed to improve cohesion and mechanical properties.

[0058] Furthermore, the coating method for overcoating may be rod coating, roll coating, gravure coating, knife coating, slot die coating, slurry coating, or extrusion coating, but is not limited thereto as long as it is conventionally practiced in the art.

[0059] In one example of the present disclosure, in the above step (c), the sulfide-based solid electrolyte membrane obtained in the above step (b) may be dried.

[0060] Drying can be performed at 40° C. to 90° C. Specifically, the drying temperature can be 40° C. or higher, 45° C. or higher, 50° C. or higher, 55° C. or higher, or 60° C. or higher, or 70° C. or lower, 75° C. or lower, 80° C. or lower, 85° C. or lower, or 90° C. or lower. If the drying temperature is lower than 40° C., the amount of residual solvent may be excessive, while if it is higher than 90° C., adhesive denaturation may occur due to the high drying temperature.

[0061] After forming a sulfide-based solid electrolyte membrane on the positive electrode active material layer or the negative electrode active material layer, the negative electrode or the positive electrode may be stacked on the other side of the sulfide-based solid electrolyte membrane and pressurized to produce an all-solid-state battery.

[0062] Pressurization can be performed within a pressure range that does not cause deformation or rupture of the positive electrode, sulfide-based solid electrolyte membrane, and negative electrode and allows good bonding between them. For example, the pressure during pressurization can be 300 MPa to 700 MPa, and more specifically, the pressure can be 300 MPa or more, 350 MPa or more, 400 MPa or more, 600 MPa or less, 650 MPa or less, or 700 MPa or less. When the pressure is less than 300 MPa, the interface resistance between the positive electrode or negative electrode and the sulfide-based solid electrolyte membrane may increase, and when the pressure is greater than 700 MPa, the positive electrode, negative electrode, or sulfide-based solid electrolyte membrane may deform or rupture.

[0063] battery module

[0064] The present disclosure also relates to a battery module including the all-solid-state battery as a unit cell, a battery pack including the battery module, and a device including the battery pack as a power source.

[0065] Specific examples of such devices include, but are not limited to: power tools powered by electric motors; electric vehicles, including electric vehicles (EVs), hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), etc.; electric two-wheeled vehicles, including electric bicycles (E-bikes) and electric scooters (E-scooters); electric golf carts; power storage systems; and the like.

[0066] Hereinafter, preferred embodiments of the present disclosure are described for the purpose of illustrating the present disclosure, but it will be apparent to those skilled in the art that various changes and modifications are possible within the scope of the present disclosure and technical ideas, and such changes and modifications fall within the scope of the appended patent claims.

[0067] Example

[0068] Hereinafter, preferred embodiments of the present disclosure are described for the purpose of illustrating the present disclosure, but it will be apparent to those skilled in the art that various changes and modifications are possible within the scope of the present disclosure and technical ideas, and such changes and modifications fall within the scope of the appended patent claims.

[0069] [Table 1]

[0070]

[0071] Experimental Example: Selecting a solvent that does not cause side reactions with sulfide-based solid electrolytes

[0072] As a solvent for immersing an electrode adjacent to a sulfide-based solid electrolyte membrane, experiments were conducted to identify a solvent that does not cause a side reaction with the sulfide-based solid electrolyte.

[0073] The sulfide solid electrolyte Li6PS5Cl was dispersed in the non-polar solvent butyrate (BB) and the polar solvent ethylene carbonate (EC) and the color change was observed. If there was no color change, there was no side reaction; if there was a color change, there was a side reaction.

[0074] Figure 1 These are photographs showing experimental results of selecting a solvent that does not cause a side reaction with a sulfide-based solid electrolyte in an experimental example of the present disclosure.

[0075] refer to Figure 1 , the sulfide-based solid electrolyte powder (①) showed no color change when dispersed in a butyrate (BB) non-polar solvent (②), but showed a color change when dispersed in an ethylene carbonate (EC) polar solvent (③).

[0076] It was found that the non-polar solvent butyrate (BB) does not react with sulfide-based solid electrolytes and is therefore a suitable solvent for impregnating electrodes adjacent to sulfide-based solid electrolyte membranes in all-solid-state batteries.

[0077] Example 1

[0078] (1) Manufacturing the negative electrode

[0079] Carbon black as a conductive material and polyvinylidene fluoride (PVDF) as a binder were mixed with N-methyl-2-pyrrolidone (NMP) solvent to prepare a slurry for forming a non-anodic coating. In this case, the conductive material and the binder were used in a weight ratio of 90:10, and the slurry was prepared to have a solid content of 45% by weight.

[0080] The slurry for forming the non-anodic coating was coated on one side of a stainless steel (SS) substrate and then vacuum-dried at 100° C. for 10 hours to form the non-anodic coating.

[0081] Using a micropipette, the non-polar solvent was allowed to disperse and wet the anodic-free coating layer, thereby impregnating the non-polar solvent butyrate (BB, dielectric constant: 5) into the anodic-free coating layer.

[0082] (2) Formation of sulfide-based solid electrolyte membrane by external coating

[0083] Li6PS5Cl with an argyrodite structure as a sulfide-based solid electrolyte and acrylonitrile butadiene rubber (NBR) as a binder were mixed in a non-polar solvent butyrate at a weight ratio of 90:10, with a solid content of 50 wt%, to prepare a slurry for forming a sulfide-based solid electrolyte membrane.

[0084] The slurry for the sulfide-based solid electrolyte membrane was applied to the non-anode coating layer, overcoated with a bar coater, and vacuum-dried at 70° C. for 5 hours to form a sulfide-based solid electrolyte membrane.

[0085] (3) Manufacturing all-solid-state batteries

[0086] The positive electrode was stacked on a sulfide-based solid electrolyte membrane and pressurized at 600 MPa to produce an all-solid-state battery. The positive electrode was prepared as follows: the positive electrode active material (LiNi 0.8 Co 0.1 Mn 0.1 The cathode active material layer was applied to an Al foil cathode current collector and roll-pressed. The residual nonpolar solvent content in the negative electrode was 443 ppm.

[0087] Comparative Example 1

[0088] The operation was carried out as in Example 1, except that the anode coating was not impregnated with the nonpolar solvent. The residual nonpolar solvent content in the negative electrode was 32 ppm.

[0089] Comparative Example 2

[0090] An all-solid-state battery was prepared in the same manner as in Example 1, except that the non-polar solvent butyrate was used instead of the polar solvent ethylene carbonate (EC, dielectric constant 85) to impregnate the anode-free coating. Due to the side reaction of the polar solvent with the coated sulfide-based solid electrolyte membrane, the battery performance and solvent content could not be evaluated.

[0091] Comparative Example 3

[0092] An all-solid-state battery was prepared using the same method as in Example 1, except that the anodic coating layer was prepared without impregnation with a nonpolar solvent. A slurry for forming a sulfide-based solid electrolyte membrane was formed on a PET substrate, and the anodic coating layer and the sulfide-based solid electrolyte membrane were pressurized and bonded. The bonding process was followed by a transfer process, resulting in the formation of a sulfide-based solid electrolyte membrane on the anodic coating layer. In this case, the anodic coating layer was not exposed to the nonpolar solvent. The residual nonpolar solvent content was 7 ppm.

[0093] Experimental Example 1

[0094] The contents of the residual non-polar solvent in the negative electrodes of the all-solid-state batteries prepared in the examples and comparative examples were compared.

[0095] After manufacturing the all-solid-state battery, the content of the non-polar solvent remaining in the anode-free coating of the negative electrode was measured by headspace GC / FID (headspace gas chromatography with flame ionization detection) analysis. The sample for solvent measurement was formed to include a positive electrode and a negative electrode, and a sulfide-based solid electrolyte membrane formed between them by overcoating.

[0096] As shown in Table 1 above, a relatively higher content of residual non-polar solvent in the negative electrode was measured for Example 1 compared to Comparative Examples 1 to 3.

[0097] In Comparative Example 1, the process of impregnating the non-anodic coating layer with a non-polar solvent was not performed, but residual non-polar solvent was measured. This is because a non-polar solvent was used in preparing the slurry during the process of forming the sulfide-based solid electrolyte membrane by overcoating.

[0098] In addition, in Comparative Example 2, the anode-free coating was not impregnated with a non-polar solvent but with a polar solvent. Due to the side reaction of the polar solvent with the coated sulfide-based solid electrolyte membrane, the battery performance and the solvent content could not be evaluated.

[0099] Furthermore, in Comparative Example 3, the anodic coating layer and the sulfide-based solid electrolyte membrane were formed separately and then bonded together, rather than impregnating the anodic coating layer with a nonpolar solvent. A small amount of residual nonpolar solvent was detected. The small amount of residual nonpolar solvent in the negative electrode was contained in the sulfide-based solid electrolyte membrane.

[0100] Experimental Example 2

[0101] The interfaces between the non-anodic coating layer and the sulfide-based solid electrolyte membrane were observed in the all-solid-state batteries prepared in Example 1 and Comparative Example 1. The interfaces were observed using a scanning electron microscope (SEM, JEOL, IT-800).

[0102] Figure 2 1 is a SEM photograph of the interface between the non-anode coating layer and the sulfide-based solid electrolyte membrane in the all-solid-state batteries prepared in Example 1 and Comparative Example 1 of the present disclosure.

[0103] refer to Figure 2, it can be seen that compared with Example 1, there are many particle agglomerates (30) at the interface between the non-anodic coating layer (10) and the sulfide-based solid electrolyte membrane (20). When forming the sulfide-based solid electrolyte membrane, during the process of coating the slurry, as the components of the slurry are squeezed out and try to penetrate the non-anodic coating layer, these particle agglomerates accumulate at the interface. The slurry components accumulated at the interface can be mainly small and light electrolyte particles, binder, etc.

[0104] On the other hand, in Example 1, such particles were difficult to observe at the interface because the non-anodic coating layer in Example 1 was impregnated with a non-polar solvent, butyrate (BB), which prevented the slurry components from being squeezed out and penetrating the non-anodic coating layer.

[0105] In the case of Comparative Example 2, a polar solvent ethylene carbonate (EC) was used instead of the non-polar solvent butyrate (BB) used in Example 1, but it was impossible to observe the interface because a side reaction occurred between the polar solvent ethylene carbonate (EC) immersed in the non-anodic coating layer and the sulfide-based solid electrolyte membrane coated on the non-anodic coating layer, resulting in decomposition.

[0106] Although the present invention has been described above with limited examples and drawings, the present invention is not limited thereto, and various modifications and changes may be made by those skilled in the art within the technical idea of ​​the present invention and the equivalent scope of the claims.

[0107] [reference numerals]

[0108] 10: No anodic coating

[0109] 20: Sulfide electrolyte membrane

[0110] 30: Particle agglomerates

Claims

1. An all-solid-state battery comprising a positive electrode, a negative electrode, and a sulfide-based solid electrolyte membrane disposed therebetween. in, The positive electrode active material layer or the negative electrode active material layer contained in the positive electrode or the negative electrode is solvent-free or contains a non-polar solvent, Wherein, the dielectric constant of the non-polar solvent is less than 10.

2. The all-solid-state battery according to claim 1, wherein The non-polar solvent includes at least one selected from the group consisting of toluene, xylene, anisole, benzene, hexane, heptane, nonane, decane, dibromomethane, dichloromethane, chloroform, butyrate, and acetate.

3. The all-solid-state battery according to claim 1, wherein The content of the non-polar solvent is 100 to 2000 ppm.

4. The all-solid-state battery according to claim 1, wherein The sulfide-based solid electrolyte membrane includes a sulfide-based solid electrolyte having an argyrodite structure.

5. The all-solid-state battery according to claim 1, wherein The sulfide-based solid electrolyte includes Li 7-x PS 6-x A x , wherein A is Cl, Br, I, Sn or a combination thereof, and x is 0≤x≤2.

6. The all-solid-state battery according to claim 1, wherein: The negative electrode active material layer contains lithium metal or is free of anode coating.

7. A method for manufacturing an all-solid-state battery, comprising: (a) impregnating a positive electrode active material layer or a negative electrode active material layer contained in a positive electrode or a negative electrode with a nonpolar solvent; (b) coating the positive electrode active material layer or the negative electrode active material layer obtained in the above step (a) with a slurry for forming a sulfide-based solid electrolyte membrane to form a sulfide-based solid electrolyte membrane; and (c) drying the sulfide-based solid electrolyte membrane obtained in the above step (b), Wherein, the dielectric constant of the non-polar solvent is less than 10.

8. The method for manufacturing an all-solid-state battery according to claim 7, wherein: The slurry for forming a sulfide-based solid electrolyte membrane is prepared by mixing a sulfide-based solid electrolyte with a solvent.

9. The method for manufacturing an all-solid-state battery according to claim 8, in, The solvent is a non-polar solvent, Wherein, the dielectric constant of the non-polar solvent is less than 10.

10. The method for manufacturing an all-solid-state battery according to claim 8, wherein: The slurry also includes a binder.

11. The method for manufacturing an all-solid-state battery according to claim 7, wherein: The outer coating is performed by rod coating, roll coating, gravure coating, knife coating, slot die coating, slurry coating or extrusion coating.

12. The method for manufacturing an all-solid-state battery according to claim 7, wherein: The drying in step (c) is performed at 40°C to 90°C.

Citation Information

Patent Citations

  • Massage apparatus having biometric information sensing means

    KR1020230106058A